2011
DOI: 10.5562/cca1751
|View full text |Cite
|
Sign up to set email alerts
|

Effects of n–3 Supplementation on Plasma and Liver Phospholipid Fatty Acids Profile in Aged Wistar Rats

Abstract: Abstract. The effects of fish oil supplementation in Wistar rats are focused on cardiovascular, endocrine, metabolic and antioxidant status changes. We determined plasma and liver phospholipid fatty acids (FAs) status and plasma lipid concentrations in aged Wistar rats. Our results showed differences in plasma and liver FAs profiles as well as plasma chlolesterol (CHOL), triglicerides (TG), high density lipoproteins (HDL), low density lipoproteins (LDL), CHOL/HDL ratio (risk factor for atherosclerosis) and LDL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 37 publications
4
9
0
Order By: Relevance
“…The same is true regarding plasma LDL-C in the present experiment (0.75 mmol/l; Figure 2): the results of the similar experiments with the FO-fed rats are between 1.84 mmol/l (Xiao et al 2012) and 0.23 mmol/l (Popovic et al 2011), the value reported by Campioli et al 2012 (0.81 mmol/l) being very similar to our data.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The same is true regarding plasma LDL-C in the present experiment (0.75 mmol/l; Figure 2): the results of the similar experiments with the FO-fed rats are between 1.84 mmol/l (Xiao et al 2012) and 0.23 mmol/l (Popovic et al 2011), the value reported by Campioli et al 2012 (0.81 mmol/l) being very similar to our data.…”
Section: Discussionsupporting
confidence: 93%
“…Plasma cholesterol. Plasma TC level of the FOfed rats in the present experiment (1.07 mmol/l; Figure 2) is approximately in the middle of the range of the results of similar experiments (FO-fed rats; all data recalculated to mmol/l): 3.22 (Lu et al 2011) → 2.45 (Ferramosca et al 2012) → 2.36 (Xiao et al 2012) → 2.04 (Campioli et al 2012) → 1.01 (Yamazaki et al 2011) → 0.98 (Takahashi 2011) → 0.54 (Popovic et al 2011).…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…8 The generation of reactive oxygen species (ROS) and reactive nitrogen species (RNS) is a normal process in the life of aerobic organisms; in fact, ROS and RNS are continually produced as a consequence of aerobic metabolism: up to 5 % of oxygen reacting with the respiratory chain is incompletely reduced to ROS. 9 Aging process is remarkably slow, indicating that even the aged animals or elderly have adopted a nearly stable state of redox homeostasis. 3 The inverse correlation found between the lifespan and n-6/n-3 ratio in membrane phospholipids, suggest different effects of n-6 and n-3 PUFA in living systems.…”
Section: Introductionmentioning
confidence: 99%